(3QSGdI aj JQLeI QVhGf Hf YHO Gddg GdLfhis - (3eMeO Hf GdWjH Hf YHO GdSdGe GdMSfj GdbGOQj , CHh YHO Gddg,J (B1187 (3g` s; (3CMeO Hf Ydj GdThSj GdHhSYjOjs
(3ChdgG (B:s
(3GdMeO ddg hef HOd GdefGUMI ai aYd GdeUGaMI JCdja CMeO Hf Ydi GdThSi GdHhSYjOi QVi Gddg Yfg eG fUg hCeG QVhGf agh QMeg Gddg QVhGf Hf YHO Gddg s
(3BNQgG (B:s
(3haGJg QMeg Gddg ai JSYjf ef GdYGTQ HfUg ef NW GdYdGeI SjOi eMeO Hf GdWjH GdaGSi GdMSjfi QMeg Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(370 d) s
Keywords: (3GdeLGejYs